Patrick's day - O'Donnell, Elizabeth Lee (Morrow Junior Books, 1994)
Patrick, always well-behaved because he thought that his town's Saint Patrick's Day parade was in his honor, tries being naughty like any ordinary boy but finds that he does not like it.